PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING ( Studi Pada CV. Manfaat Di Ambarawa ) - Ibnu Alwan, Habib; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2018)
Employee performance is influenced by the various personal traits of each individual. In a competitive and globalized development, the company needs high-performing employees. People with high levels of performance are referred to as productive people, and conversely people who do not reach the standard level are said to be unproductive or low performing. Many factors can affect employee performance, such as compensation and job satisfaction. The purpose of this study is to analyze the effect of compensation on employee performance with job satisfaction as intervening.Population used is employees of production CV. Manfaat, Jl. Ambarawa-Magelang KM 3, Gondoriyo, Jambu which amounted to 203 employees. Samples taken 67 employees. The type of data used in the primary data. Methods of data collection questionnaire. Analyti cal technique used was path analysis, previously tested by instrument test and classical assumption test.The research result showed that: Compensation proved to have effect positive and significant on job satisfaction. Job satisfaction proved to have effect positive and significant on employee performance. Compensation proved to have effect positive and significant on employee performance. Compensation proved to have effect on employee performance with job satisfaction as intervening variable.